PERHITUNGAN BEBAN PENDINGIN PADA RUANG SIDANG FAKULTAS TEKNIK UNSRAT - Vernando V Sasuang; Frans P Sappu; Hengky Luntungan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2018)
Air conditioning is a cooling system where heat is transferred from the room to the atmosphere. In conducting activities in the room humans require conditions comfortable, the temperature or the humidity of the air in the room. To achieve comfortable conditions in a room, it is necessary to do air conditioning by using a cooling machine so that comfortable air can be obtained. Meeting Room of Faculty of Engineering Sam ratulangi University is often used as a place to carry out various activities, thus requiring cooling system. In this final project a calculation is performed to determine the peak cooling load and then determine the capacity of the cooling machine used to cool the room.From the calculation results obtained by the peak cooling load on the room = 125.301,3 BTU/jam. If using an Air Conditioning (AC) engine with 2 PK, then AC is required during peak load in the room as much as 7 unitsÂ Keywords: Air conditioning, Cooling load, Cooling machine